Mapping Urban Transformation: The Random Forest Algorithm to Monitor Land Use and Land Cover Change in Bandar Lampung City - Darmawan, Arief; Santoso, Trio (Jurnal Sylva Lestari, 2024)
Bandar Lampung City has substantially altered its land cover due to rapid urbanization in the past decade. Landsat 8 OLI is suitable for conducting land cover change research and offers current and precise data on the present land cover. This research aimed to monitor and analyze the changes in seven categories of land use and land cover (LULC): forest, agricultural land, rice field, settlement, water body, bare land and industrial area. The land use and land cover (LULC) in Bandar Lampung City were analyzed using Landsat 8 OLI satellite images from 2013 to 2023. The Random Forest Algorithm was employed for this analysis. The LULC model assessment was carried out with a confusion matrix, resulting in almost perfect agreement for the 2013 and 2023 LULC models. The LULC classes showed an area growth in settlement of 5,526.25 ha (29.12%) and agricultural land of 1,071.63 ha (5.30%) but opposite with forest class that experienced significant area loss that reached 2,012.35 ha (-26.02%) and waterbody and industrial area 285.64 (-6.15%) and 167.67 ha (-4.04%), respectively. The findings reveal significant shifts in forest and agricultural land, highlighting the region’s rapid urbanization and deforestation patterns. These changes have practical implications for environmental management and urban planning, suggesting the need for sustainable LULC policies to prevent the impacts of rapid LULC transformations on ecosystem services and local communities. Keywords: Bandar Lampung, K-nearest neighbors, land use and land cover change, QGIS 3.20, random forest algorithm